The Alignment between Learning Outcomes and Assessment Tasks in Writing: A BRT Analysis - Fauziana Ulfie; Sudarya Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2021)
This study was aimed at obtaining the profile of alignment between learning outcomes and assessment tasks on ‘writing’ skills development in “Pathway to English Grade X” textbook with regards to Bloom’s Revised Taxonomy. The data of the study were 32 statements of learning outcomes and 49 items of assessment tasks of 10 chapters. This study used Bloom’s Revised Taxonomy table (Anderson & Krathwohl, 2001) as the framework of reference in conducting data collection and interpretation. The results showed that the LOs and ATs distributed over several levels. 34.38% of overall LOs of this textbook are described in level B4 (Analyze, Conceptual Knowledge), and 22.45% of overall ATs are described in level B2 (Understand, Conceptual Knowledge). In the textbook, it was found that 69.39% of the overall ATs match with the LOs in the textbook. 20.41% of the overall ATs partially match with the LOs, and 10.20% of the overall ATs do not match with the LOs in the textbook. The results showed that the alignment between the learning outcomes and assessment tasks on ‘writing’ skills development in this textbook is strong or the percentage is more than 50%.